2019
DOI: 10.1016/j.quageo.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

pIRIR and IR-RF dating of archaeological deposits at Badahlin and Gu Myaung Caves – First luminescence ages for Myanmar

Abstract: Reliable chronologies are essential for understanding the timing and routes of human dispersal through Southeast Asia, both of which remain open questions. This study provides luminescence chronologies for two archaeological sites in Myanmar-Badahlin Cave and Gu Myaung Cave-from which Palaeolithic artefacts have been recovered. We applied single-grain post-infrared infrared stimulated luminescence (pIRIR) and multi-grain infrared-radiofluorescence (IR-RF) dating methods to potassium-rich feldspar (Kfeldspar) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Radiocarbon-and luminescence-based chronologies from Tham Lod and Ban Rai rockshelters suggested forager occupations extending into the Late Pleistoceneover 30 000 years ago at Tham Lod-but only a sporadic Holocene occupation. More recent analyses show a similar trend: luminescence ages from Badahlin Cave in Myanmar indicate human occupation in the Pleistocene, and radiocarbon measurements from Doi Pha Kan in Thailand date to the Terminal Pleistocene (Imdirakphol et al 2017;Schaarschmidt et al 2019). Evidence for Holocene foragers in north-west Thailand is less well-established.…”
Section: Introductionmentioning
confidence: 94%
“…Radiocarbon-and luminescence-based chronologies from Tham Lod and Ban Rai rockshelters suggested forager occupations extending into the Late Pleistoceneover 30 000 years ago at Tham Lod-but only a sporadic Holocene occupation. More recent analyses show a similar trend: luminescence ages from Badahlin Cave in Myanmar indicate human occupation in the Pleistocene, and radiocarbon measurements from Doi Pha Kan in Thailand date to the Terminal Pleistocene (Imdirakphol et al 2017;Schaarschmidt et al 2019). Evidence for Holocene foragers in north-west Thailand is less well-established.…”
Section: Introductionmentioning
confidence: 94%
“…3). Varma et al (2013) reported that although the IR-RF signal of their sample was almost at its saturation level, it did not show significant phosphorescence after bleaching the sample for 800 s. Hence, they concluded that no extra pause is needed and suggested that a delay of 500 s is sufficient to reduce the phosphorescence down to the background level if the bleaching time is less than 800 s. Similarly, Schaarschmidt et al (2019) reported a weak phosphorescence compared to the IR-RF signal and reduced the pause to 900 s for their samples.…”
Section: Phosphorescencementioning
confidence: 99%
“…In summary, it seems that phosphorescence caused by bleaching can be avoided by introducing a pause of 15 min to 1 h prior to IR-RF measurements (Erfurt and Krbetschek, 2003b;Frouin et al, 2015;Schaarschmidt et al, 2019) in the case of solar simulator bleaching and may not be required if the sample is bleached with a UV LED for 800 s or longer (Varma et al, 2013).…”
Section: Phosphorescencementioning
confidence: 99%
“…Different methods were applied to overcome the fading problem, such as the fadia method [119][120][121], the isochron method [122], isolating 'zero'-fading grains [123], and fading correction [124,125]. After the pIRIR dating protocol was established, single-grain pIRIR dating with K-feldspar has been reported in numerous studies [43,108,[126][127][128][129][130][131][132][133][134][135][136][137]. The machine time can be saved by performing prior-IR stimulations on all the grains simultaneously [108,129,137].…”
Section: Single-grain Datingmentioning
confidence: 99%